BIAYA PENGGUNAAN OBAT HIPOGLIKEMIK ORAL (OHO) METFORMIN DAN GLIMEPIRID PADA PASIEN DIABETES MELITUS TIPE II RAWAT JALAN NON BPJS DI SERANG TAHUN 2018 TIDAK BERBEDA SIGNIFIKAN - Aprilla Ayu Wulandari; Rika Revina; Dhigna Luthfiyani Citra Pradana (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Diabetes mellitus (DM) is one of the four priorities of non-communicable diseases in the world, divided into two types (I and II). The incidence of type II DM in Serang is quite high, there were more than 500 outpatients in 2018, with around 70-100 non BPJS patients. This research was conducted to non BPJS patients, in order to see the difference in the cost of using Oral Hypoglycemic Drugs (OHDs), namely Metformin and Glimepirid. Similar research has never been done by UPN Veterans Jakarta in Serang. This study was an observational analytic study using a cross-sectional approach whose data were taken retrospectively. Subjects were non BPJS type II DM outpatients in 2018, aged 20-65 years, and adhering to treatment using Metformin and Glimepirid. The tools used are paper, stationery, computers, and printers. The materials used are patient data obtained from medical records, pharmaceutical installations, and finance. Data were analysed descriptively and tested its normality with Kolmogorov-Smirnov. The results showed the average cost of using Metformin was Rp 1,209,- while Glimepirid was Rp 1,228,-. So it can be concluded that the cost of using Metformin in outpatient type II DM patients in Serang in 2018, is slightly cheaper than Glimepirid.